Late Holocene expansion of Siberian dwarf pine (Pinus pumila) in Kamchatka in response to increased snow cover as inferred from lacustrine oxygen-isotope records - Hammarlund D.; Klimaschewski A.; St Amour N.; Andrén E.; Self A.; Solovieva N.; Andreev A.; Barnekow L.; Edwards T. (2015)
© 2015 Elsevier B.V. Holocene records of cellulose-inferred lake-water δ18O were produced from two lake-sediment sequences obtained in central and northern Kamchatka, Russian Far East. The sediment records share similar fluctuations in δ18O during the interval of ca. 5000-800calyr BP that correspond (inversely) with changes in K+ content of the GISP2 ice-core record from Greenland, a proxy for the relative strength of the Siberian High, suggesting control by climate-related variability in δ18O of regional precipitation. The dramatic expansion of Siberian dwarf pine (Pinus pumila) in northern and central Kamchatka between ca. 5000 and 4000calyr BP, as inferred from pollen records from the same and neighbouring sites, appears to have occurred at a time of progressively declining δ18O of precipitation. This development is interpreted as reflecting a regional cooling trend accompanied by increasing winter snowfall related to gradual intensification of the Siberian High from ca. 5000 to ca. 3000calyr BP. A thicker and more long-lasting snow cover can be assumed to have favoured P. pumila by providing a competitive advantage over other boreal and subalpine tree and shrub species in the region during the later part of the Holocene. These results, which are the first of their kind from Kamchatka, provide novel insight into the Holocene vegetational and climatic development in easternmost Asia, as well as long-term atmospheric circulation dynamics in Beringia.